No U-turn needed on the elected presidency - EUGENE, Tan K. B. (Institutional Knowledge at Singapore Management University, 2016)
SMU Associate Professor of Law Eugene Tan cited the commentary "Let's talk about policy failures and the elected presidency" by Professor Kishore Mahbubani, where the latter argued that Singapore’s policy of an elected presidency should be revisited, and perhaps "the time has come to do a U-turn", stop having direct elections and go back to the previous practice of having Parliament elect the president. While Associate Prof Tan noted that Prof Mahbubani's concern is legitimate, he emphasised that the way forward is not a U-turn, but rather, a collective effort to determine how we can reduce the likelihood of electing a rogue president, while enhancing the elected presidency as a sentinel to good governance.